Prototyping IoT-Based Safety Telemetry System for Forest Firefighters - Eka Wahyudi; Novi Indah Pradasari; Ar-Razy Muhammad; Darmanto; Dedy Hidayat Kusuma; Indra Pratiwi; Herman (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
Forest fires significantly impact the environment, carbon emissions, and public health. Ensuring the safety of forest firefighters remains a critical challenge, as they operate in high-risk environments with limited communication infrastructure. This study develops an Internet of Things (IoT)-based safety telemetry system utilizing LoRa communication to monitor firefighters’ physiological and environmental conditions in real time. The system is built on an ESP32 microcontroller integrated with sensors for body temperature, heart rate, ambient temperature and humidity, CO and CO₂ concentrations, as well as a GPS module for location tracking. Sensor data are transmitted via a LoRa SX1278 module to a Raspberry Pi–based gateway and subsequently forwarded to a cloud server for visualization and monitoring. System performance was evaluated in forested and residential environments over distances of up to 1 km. The results demonstrated an average data transmission success rate of 97% with a latency of 1.47 seconds, indicating reliable LoRa communication in areas with limited cellular network coverage. Furthermore, the sensors achieved measurement errors below 3%, while the system operated continuously for 12.5 hours with a power consumption of only 0.68 W, demonstrating high accuracy, reliability, and energy efficiency. The system also provides an early warning mechanism for hazardous conditions encountered by firefighters. User evaluations revealed an 89% satisfaction rate, particularly regarding the effectiveness of the early warning feature and overall system usability. These findings demonstrate that the proposed LoRa-based IoT telemetry system can effectively enhance firefighter safety through accurate, reliable, and energy-efficient real-time monitoring.